2019
DOI: 10.55151/ijeedu.v1i2.15
|View full text |Cite
|
Sign up to set email alerts
|

Comfort Temperature and Lighting Intensity: Ergonomics of Laboratory Room Machine Tools

Abstract: Laboratories that meet ergonomic standards will support the learning process, both academically and technically, to facilitate the growth and development of skills. This study aims to uncover and provide an overview and information about laboratory ergonomics standards which include thermal comfort (temperature), workspace laboratory lighting. This study uses a quantitative approach with a survey method carried out in the Machine Tool Unit Laboratory of the Department of Mechanical Engineering Education with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The influence of temperature on staff physical and mental work performance varies based on the nature of the work environment and tasks (Idkhan & Baharuddin, 2019). In the trauma room, proper temperature should be prioritized for patient comfort and then staff comfort, both of which can have implications for patient safety in the form of hypothermia or staff task disruption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of temperature on staff physical and mental work performance varies based on the nature of the work environment and tasks (Idkhan & Baharuddin, 2019). In the trauma room, proper temperature should be prioritized for patient comfort and then staff comfort, both of which can have implications for patient safety in the form of hypothermia or staff task disruption.…”
Section: Discussionmentioning
confidence: 99%
“…Proper lighting provides an improved and invigorating atmosphere to minimize work exhaustion and improve productivity (Idkhan & Baharuddin, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most workstations need additional lighting so that workers can do their work optimally. The tendency for lighting to be less than the standard set can impact a lack of concentration and stress at work [4].…”
Section: Introductionmentioning
confidence: 99%
“…Aflaki et al [15] assessed the indoor environment in a traditional library building and indicated poor lighting conditions-with the light intensity in the reading zone found to be below 300 lux. Idkhan and Baharuddin [37] conducted a study on sixty students in the laboratory of a traditional university building in Indonesia. The average light intensity amounted to 422.14 lux, which was below the national standard requirement.…”
Section: Introductionmentioning
confidence: 99%